A Diagnostic Surprise: Primary Hodgkin's Lymphoma of the Lung - Ankur Sinha MBBS; Ravikaran Patti MBBS; Prabhsimranjot Singh MD; William Solomon MD; Yizhak Kupfer MD (SAGE Publishing, 2017)
An 81-year-old male presented to the emergency room with a 3-month history of progressive shortness of breath, productive cough with white sputum, and generalized weakness with 10-pound weight loss in 2 months. On presentation, the patient was afebrile, with blood pressure of 93/55 mm Hg and oxy-hemoglobin saturation of 92% on 2 liters of oxygen via nasal cannula. Complete blood count with differential was significant for white count of 12 400/mL. Brain natriuretic peptide level was 454 ng/mL. Postero-anterior chest radiograph showed multiple round opacities in the lung fields. Computed tomography scan of the chest confirmed multiple round densities in both the lung fields along with mild mediastinal lymphadenopathy. Core needle biopsy was performed. Immunohistochemical stains were positive for CD30 and CD15 in a population of large atypical cells amid a background of CD3-positive nonneoplastic cells. These results were in support of the diagnosis of classical Hodgkin's lymphoma of the lung with histological appearance confirming nodular sclerosis type. The patient was started on chemotherapy but was readmitted in 20 days for acute respiratory distress and suffered cardiac arrest and subsequently died. This case highlights the fact that although primary pulmonary Hodgkin's lymphoma of the lung is a rare entity, it should be thought of as a differential while evaluating lung masses. In these cases, definite diagnosis can only be made by biopsy and histology. Early commencement of chemotherapy and regular follow-up with oncology is essential.